(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The purpose of this research was to investigate the role of impulsive behavior in the prediction of the emotional/behavioral problems of adults with intellectual disability (ID). The statistical population included all adults with ID who were being trained in vocational rehabilitation centers, supported by the State Welfare Organization of Iran and the educational organization for children with special needs, in Shahrekord, Iran, in 2017-2018. The sample consisted of 134 adults with ID, selected through convenience sampling. The Barratt Impulsiveness Scale Version 11 (BIS-11) was used for measuring the impulsive behavior and The Developmental Behavior Checklist for Adults was used for measuring the emotional and behavioral problems. The collected data were analyzed using the Pearson correlation coefficient and simultaneous multiple regression. The results showed that impulsive behavior was a positive and significant predictor for emotional/behavioral problems and its subscales (P<0.01). Impulsive behaviors could predict emotional/behavioral problems such as self-absorbed problems, disruptive problems, antisocial problems, depressive problems, communication and anxiety disturbance and social relating problems. Therefore, designing and implementing preventive and interventional programs to improve the impulsive behavior of adults with ID appears to be necessary to reduce their emotional/behavioral problems.